Sytuacja prawnomiędzynarodowa Wysp Alandzkich w Unii Europejskiej - Brańka, Tomasz (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2017)
Wyspy Alandzkie są szwedzkojęzycznym terytorium autonomicznym Finlandii. Szeroka autonomia, przyznana na mocy decyzji Ligi Narodów z 1921 r., umożliwiła samodzielne podjęcie decyzji dotyczącej integracji bałtyckiego archipelagu ze Wspólnotami Europejskimi na początku lat 90. ubiegłego wieku. Artykuł przedstawia proces dochodzenia do członkostwa Wysp Alandzkich, skupiając się na szczególnym statusie, jaki przyznano archipelagowi. Dzięki wspólnemu zaangażowaniu władz autonomicznych i władz centralnych Finlandii oraz przychylnej postawie WE udało się wypracować derogacje, które w swojej istocie dotykają podstawowych zasad tej organizacji. W ten sposób Alandczykom udało się zabezpieczyć nie tylko szwedzkojęzyczny charakter Wysp (utrzymanie prawa domicylu), ale także zapewnić ochronę własnej gospodarki (wyłączenie z ustaleń w zakresie unijnego prawa podatkowego).

The Åland Islands are a Swedish-speaking autonomous territory of Finland. The broad autonomy granted by the League of Nations’ decision of 1921 allowed the Isles to make an independent decision on the integration of the Baltic archipelago into the European Communities in the early 1990s. The article presents the process of the Åland Islands obtaining EC membership, and focuses on the special status awarded to the archipelago. Thanks to the joint involvement of the autonomous authorities of the Islands and central authorities of Finland and the favorable attitude of the EC, derogations were successfully developed which, in essence, concern the basic principles of the EC. By this token, the citizens of the Åland Islands managed to secure not only the Swedish-speaking nature of their territory (retaining rights of domicile), but also the protection of their own economy (being excluded from the EU tax law regulations).
The status of the Åland Islands in the European Union under international law
Keywords: Wyspy Alandzkie; Unia Europejska; prawo domicylu; autonomia; Aland Islands; European Union; right of domicile; autonomy